Cell Selection Algorithm for Edge Users in Heterogeneous Wireless Network - Zhendong Zhao; Weijiao Niu; Dongsheng Han; Shasha Ding (Dianxin kexue)
A large number of “cell-edge area”can arise when deploying a variety of low-power base stations in heterogeneous networks, this can affect the property of edge users. So a cell selection algorithm for edge user was proposed, by using the transmitting end to precoding to suppress interference and improve user received signal-to-interference-plus-noise-ratio（SINR）. According to the current number of user in the cell, dynamically adjust the reference received signal added bias to the picocell edge users, to avoid edge users accessing heavy loaded cells. The simulation results show that, compared with the reference algorithms, the proposed algorithm can effectively reduce the load of macrocells, balance the load between different picocells and improve the throughput and resource utilization of the light load picocells.